A PC based state estimator interfaced with a remote terminal unit placement algorithm. - Yehia, M. (IEEE Transactions on power systems)
In this paper a new remote terminal unit (RTU) placement algorithm is presented. The objective of this algorithm is to place a minimum set of RTUs which satisfies three important constraints of the problem-observability, absence of critical measurements, and reliability requirements defined in terms of RTU loss. The problem is solved in a single stage. The results of this algorithm are interfaced with a linear programming (LP) state estimator. This estimator only uses the voltage measurements, and the active and reactive power flows in the lines for the development of the coupled state-estimation Jacobian H-matrix. The injection measurements are not currently included, though in practice they can be easily added to the estimator model. The inclusion of the injection measurements will enlarge the use of the presented algorithm. The RTU placement algorithm and its link with the LP estimator are tested on IEEE standard bus systems. Using the proposed RTU set, the test results presented show that the LP estimator has very good filtering capabilities when operated with or without bad data, and that the loss of any RTU does not have any significant impact on the solution